Blanching effect on the bioactive compounds and on the viability of Lactobacillus rhamnosus GG before and after in vitro simulation of the digestive system in jabuticaba juice - Oliveira, Daniane Campos de; Martins, Eliane Maurício Furtado; Martins, Maurilio Lopes; Martins, Giovanna Bretas; Binoti, Mirella Lima; Campos, André Narvaes da Rocha; Ramos, Afonso Mota; Silva, Maurício Henriques Louzada; Stringheta, Paulo César (Semina: Ciências Agrárias, 2017)
The viability of Lactobacillus rhamnosus GG (LGG) in jabuticaba juices and its survival in the gastrointestinal tract (GIT), simulated in vitro, was studied. Two juices were prepared: A - with non-blanched fruits, and B - with blanched fruits. LGG was then added and the juices maintained at 8 ºC for 28 days. The control treatment consisted of juices without the added probiotic. The following were determined in the juices: the viability and in vitro survival of LGG, fecal coliforms, Salmonella sp., pH, acidity, total soluble solids (TSS), color, antioxidant capacity, total phenolic compounds, anthocyanins and ascorbic acid. The sensory acceptability was also determined using a 9-point hedonic scale. Blanching interfered (p < 0.05) with the viability of LGG, juice A showing the greatest viability as compared to juice B. After in vitro simulation, the probiotic bacterial count was < 1.0 log CFU mL-1, which demonstrates the low resistance of the strain to the simulated GIT conditions. The juices were conformed to the microbiological standards established by law. The pH, acidity and TSS were influenced by blanching (p < 0.05), with values of 5.03, 0.46% and 15.38 Â°Brix for juice A and 5.12, 0.66% and 16.05 Â°Brix for juice B, respectively. The addition of LGG did not influence these characteristics. Only the pH value was influenced by the storage time (p < 0.05), increasing throughout storage. Juice B showed lower luminosity (L*) and a greater value for a* as compared to juice A, indicating that the former became darker and redder due to the blanching process. Both juices showed positive values for the b* coordinate. The juice was found to be a good source of polyphenols. Neither the time nor the addition of LGG affected the antioxidant capacity, total phenolic compounds or anthocyanin contents. However, blanching contributed (p < 0.05) to an increase in the contents of these compounds in the juices. Values for antioxidant capacity of 186.20 and 2552.59 uM Trolox g-1, for total phenolic compounds of 275.06 and 1163.18 mg GAE 100 g-1-wwb, and for anthocyanins as cyanidin 3-glucoside of 12.71 and 90.99 mg 100 g-1 were found for juices A and B, respectively. The juices contained 72.87 mg 100 mL-1 of ascorbic acid. Scores of above 6.0 (liked slightly) were awarded on the hedonic scale for the attributes evaluated. The addition of probiotics in jabuticaba juices needs to be further studied to ensure the viability of the cultures during storage and their survival in the gastrointestinal tract.